Sexualidades dissidentes em prosa: as representações das homossexualidades masculinas e das travestis na década de 1970 nos jornais de Belém/PA - CASTRO, Alana Albuquerque de (Universidade Federal do Pará, 2023)
The civil-military coup took place in 1964, and it would last until mid-1985, the year which would mark the beginning of a series of social, political, cultural and economic changes. During this period, more specifically in the 70's, homosexuality would rise to a prominent place, not only in Brazil but in the entire world. The gay power movement and the Sexual Revolution would bring to light an entire generation which was tired of hiding and denying its own desires. In this context, Belém was also a stage for great changes. The "Mainstream Media" supported the military regime and all of its "morality". On the other hand, however, Belém's youth was breaking free from its shackles and looking for ways to have their voice heard by society, either through attempts to organize themselves politically or through spaces of sociability. Homosexuality and transvestites were not invisible and these subjects were not willing to remain on the margins of society. With that said, this work seeks to comprehend what was the place of Gay Men and Transvestites in this society going through so many transformations and how these people were portrayed in the journalistic discourses about dissident sexualities made by the mainstream media (A Província do Pará, Folha do Norte/Folha Vespertina e O Liberal) in the 70's. For this, in addition to the newspapers, I conducted interviews with interlocutors who lived the period and all these changes mentioned, broadening my understanding of the dynamics of the period, the sociability, the spaces, the social political movement, the daily practices, behaviors and representations related to homosexuals and transvestites.